THE ANALYSIS OVER IMPLEMENTATION RATE OF THE FLEXIBILITY OF THE FINANCIAL MANAGEMENT PATTERN IN LOCAL PUBLIC SERVICE AGENCY (Case Study at Local Public Hospital of Kediri Regency) - Anissa Putri Ayuingtyas; Helmy Adam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The objective of research is to understand the implementation rate of the flexibility of financial management pattern in local public service agency (PPK- BLUD) at Local Public Hospital of Kediri Regency (RSUD Kabupaten Kediri). Method of research is qualitative descriptive with case study approach at RSUD Kabupaten Kediri. Data collection technique involves interview, observation and documentation. Result of research indicates that after RSUD Kabupaten Kediri is given assignment of PPK-BLUD in 2010 and implementing PPK-BLUD in 2013, the income of hospital is arising quite significant and punctual to fulfill the short-term obligation. Flexibility practiced by RSUD Kabupaten Kediri can be found in some managerial matters such as income, expense, employee, payable/receivable, the supply of goods and services, and the establishment of supervisory board. However, the Hospital is not seemingly flexible for service tariff, remuneration, investment and asset management. It is because RSUD Kabupaten Kediri is not maximizing the use of BLUD flexibility. The implementation of PPK-BLUD flexibility at RSUD Kabupaten Kediri is still impaired. The lacking of synergic understanding about the implementation of BLUD flexibility between the Government of Kediri Regency and RSUD Kabupaten Kediri has caused the Hospital to hesitate from practicing the flexibility. Keywords: Local Public Service Agency, Flexibility, Local Financial Management Pattern, Hospital